2016
DOI: 10.4028/www.scientific.net/msf.858.429
|View full text |Cite
|
Sign up to set email alerts
|

4H-SiC Surface Structures and Oxidation Mechanism Revealed by Using First-Principles and Classical Molecular Dynamics Simulations

Abstract: The 4H-SiC(000-1)C and (0001)Si surface reconstructed structures and the oxidation processes of these surfaces are investigated using a first-principles calculation method. The most stable reconstructed 4H-SiC(000-1)C and (0001)Si surfaces have p-bonded chains. In the topmost SiC bilayer, half of Si and C atoms exchange their positions and C-C or Si-Si bonds formed densely below the surfaces. When we place a SiO2 layer on the p-bonded chain (000-1)C surface, C-C bonds are formed more densely below the interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Theoretical studies using first-principles calculations have been carried out by several authors [6][7][8][9][10][11][12][13][14][15][16][17] to address this issue. Knaup et al reported that a carbon interstitial defect [carbonyl group-like structure; see Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies using first-principles calculations have been carried out by several authors [6][7][8][9][10][11][12][13][14][15][16][17] to address this issue. Knaup et al reported that a carbon interstitial defect [carbonyl group-like structure; see Fig.…”
mentioning
confidence: 99%
“…They suggested that the carbon atoms emitted from SiC substrate tend to form carbonyl groups or C clusters containing C=C double bonds. 15) We need to understand the electronic structures of these defects to verify whether they are the origin of the large D it and NIT. Because the oxide layer of the SiC=SiO 2 interface is amorphous, the C=O and C=C defects can have structural variations, which may shift the energetic position of the corresponding defect level.…”
mentioning
confidence: 99%